Genomic modelling of the ESR1 Y537S mutation for evaluating function and new therapeutic approaches for metastatic breast cancer - Harrod,A; Fulton,J; Nguyen,VTM; Periyasamy,M; Ramos,Garcia L; Lai,C-F; Metodieva,G; de,Giorgio A; Williams,RL; Santos,DB; Jimenez,Gomez P; Lin,M-L; et al. (Oncogene, 2016)
Drugs that inhibit estrogen receptor-α (ER) activity have been highlysuccessful in treating and reducing breast cancer progression in ER-positivedisease. However, resistance to these therapies presents a major clinicalproblem. Recent genetic studies have shown that mutations in the ER geneare found in >20% of tumours that progress on endocrine therapies.Remarkably, the great majority of these mutations localise to just a few aminoacids within or near the critical helix 12 region of the ER hormone bindingdomain, where they are likely to be single allele mutations. Understandinghow these mutations impact on ER function is a prerequiste for identifyingmethods to treat breast cancer patients featuring such mutations. Towardsthis end, we used CRISPR-Cas9 genome editing to make a single alleleknockin of the most commonly mutated amino acid residue, tyrosine 537, inthe estrogen-responsive MCF7 breast cancer cell line. Genomic analysesusing RNA-seq and ER ChIP-seq demonstrated that the Y537S mutationpromotes constitutive ER activity globally, resulting in estrogen-independentgrowth. MCF7-Y537S cells were resistant to the anti-estrogen tamoxifen andfulvestrant. Further, we show that the basal transcription factor TFIIH isconstitutively recruited by ER-Y537S, resulting in ligand-independentphosphorylation of Serine 118 (Ser118) by the TFIIH kinase, CDK7. TheCDK7 inhibitor, THZ1 prevented Ser118 phosphorylation and inhibited growthof MCF7-Y537S cells. These studies confirm the functional importance of ERmutations in endocrine resistance, demonstrate the utility of knockinmutational models for investigating alternative therapeutic approaches andhighlight CDK7 inhibition as a potential therapy for endocrine resistant breastcancer mediated by ER mutations.